Ixekizumab Demonstrates Rapid and Consistent Efficacy for Patients with Psoriatic Arthritis, Regardless of Psoriasis Severity - April W. Armstrong; Tarannum Jaleel; Joseph F. Merola; Alice B. Gottlieb; Saakshi Khattri; Cameron C. Helt; William N. Malatestinic; Sarah E. Ross; Marcus E. Ngantcha; Kurt de Vlam (Dermatology and Therapy, 2024)
Abstract Introduction Skin involvement in patients with psoriatic arthritis (PsA) worsens the severity and burden of disease. Ixekizumab (IXE), a selective interleukin (IL)-17A antagonist, was compared to placebo (PBO) in the SPIRIT-P1 (NCT01695239) and SPIRIT-P2 (NCT02349295) studies in patients with PsA and evidence of plaque psoriasis. This post hoc analysis reports musculoskeletal, skin, and nail outcomes through week 24 in patients from SPIRIT-P1 and SPIRIT-P2, stratified by mild, moderate, or severe psoriasis at baseline. Methods This post hoc analysis pooled patients from SPIRIT-P1 and SPIRIT-P2 who were randomly assigned to PBO or IXE 80 mg every 4 weeks (Q4W) or every 2 weeks (Q2W). Efficacy outcomes were analyzed through week 24 by baseline psoriasis severity, defined by percent body surface area (BSA) affected; mild = BSA < 3%, moderate = 3% ≤ BSA ≤ 10%, severe = BSA > 10%. The primary outcomes assessed were the proportion of patients achieving American College of Rheumatology (ACR)20, ACR50, and ACR70 responses. Secondary outcomes included musculoskeletal, disease activity, skin and nail, and health-related quality-of-life measures. Results Similar proportions of patients achieved ACR20/ACR50/ACR70 over time across all severity subgroups and treatment arms. More than one-third of IXE-treated patients achieved ACR20 at week 4, or ACR50 at week 24, with no significant differences according to psoriasis severity at baseline. Disease activity outcomes were similar through week 24 with both IXEQ4W and IXEQ2W, regardless of psoriasis severity at baseline. There were no significant differences over 24 weeks in the proportions of IXE-treated patients with mild, moderate, or severe baseline psoriasis who achieved Minimal Disease Activity (MDA). Across all severity subgroups, IXE demonstrated Psoriasis Area Severity Index 100 response as early as week 4, and approximately one-third of IXE-treated patients achieved total skin clearance at week 24. Conclusion IXE demonstrated rapid and consistent efficacy in joint, skin, and nail for patients with PsA, regardless of baseline psoriasis severity. Trial Registration SPIRIT-P1 (NCT01695239), SPIRIT-P2 (NCT02349295).